The effect of knowledge transfer theory on the selection of crossover winter sports athletes: a systematic literature review - Gao, Yongqi; Soh, Kim Geok; Zakaria, Noor Syamilah; Mohd Rasdi, Roziah; Guo, Wei; Soh, Kim Lam (Frontiers Media, 2023)
This article reviews studies on the knowledge transfer theory (KTT) in sport psychology using the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) method to identify any existing research gaps. This review utilizes a systematic process that involves searching for studies aimed at clarifying the relationship between KTT and crossover selection, promoting crossover development of winter sports, and cultivating outstanding athletes across six different databases. This work provides the foundation for future research on KTT in the field of selection of athletes for professional sports and those intending to showcase KTT’s success in the selection of winter sports athletes. This review found that crossover selection of qualified athletes helps solve the issue of the shortage of professional athletes in specific sports.